Designing and Developing a Model for Divorce Reduction through Resilience Training and Logotherapy for Couples - Javdan, Moosa; Samavi, Abdolwahab; Ahmadi, Beheshteh (Mental Health and Lifestyle Journal, 2025)
The aim of this study was to design and develop a model for reducing divorce through resilience training and logotherapy for couples. The present study was applied in purpose and conducted using a correlational method with structural equation modeling. The statistical sample consisted of 150 couples who had referred to counseling centers in Bandar Abbas due to marital conflicts. The second group included couples who had filed complaints against their spouses in court for various reasons and participated in Anderson’s (2007) logotherapy workshop and Henderson et al.’s (1997) resilience training. In this study, data collection instruments included the Couples’ Intellectual Understanding and Harmony Questionnaire by Javan (2014), the researcher-developed Divorce Inclination Scale, the Connor and Davidson Resilience Questionnaire (2003), and the Meaning in Life Questionnaire by Steger et al. (2006). Data obtained from the questionnaires were analyzed in the first phase through simple correlation coefficients among variables and structural equation modeling to test model fit and path analysis using maximum likelihood estimation. In addition, to test indirect effects in the proposed model, the bootstrap method was applied. In the second study, univariate covariance analysis (ANCOVA) and multivariate covariance analysis (MANCOVA) were used. The results of direct relationships among the research variables in the proposed model indicated that all path coefficients between variables were statistically significant. Evaluation of the proposed model showed that the Root Mean Square Error of Approximation (RMSEA) index was 0.06, indicating a good model fit with the data. Overall, 64% of the variance in divorce reduction inclination was predicted by the model’s variables. Results from MANOVA revealed that the observed Wilks’ Lambda was 5.93, which was statistically significant at p ≤ 0.001. Furthermore, post-hoc test results demonstrated a significant difference between the mean scores of the two experimental groups compared with the control group for the above-mentioned variables, while no significant difference was found between the two experimental groups. The findings revealed that marital conflicts often arise due to poor emotional regulation and hasty, extreme reactions to family problems. Resilient individuals have greater awareness and recognition of their emotions and feelings compared to others. Moreover, focusing on meaning in life provides a deeper and more accurate understanding of issues.